Gamification in English Learning: Building Students’ Motivation and Creativity - Farisca, Angel; Warni, Silih (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
This study investigates the effectiveness of gamification in English language learning, focusing on its impact on students’ motivation and creativity. In the digital age, educators are increasingly integrating game elements into instructional design to foster learner engagement and innovative thinking. This study employed an explanatory sequential mixed-methods design, combining quantitative and qualitative approaches. Quantitative data were collected through pre- and post-tests using the Academic Motivation Scale (Ryan & Deci, 1985), Tests of Creative Thinking by Torrence (2018), and a researcher-developed questionnaire assessing students’ understanding of gamification elements such as points, challenges, and badges. The participants were 33 eleventh-grade students from a public high school in Bekasi. The results showed statistically significant improvements in all three measured variables. Furthermore, semi-structured interviews revealed increased engagement, confidence, and imaginative language use during gamified learning activities. Challenges included limited access to digital devices, unstable internet connectivity, and differences in student adaptability based on prior technology exposure and personality traits. These findings suggest that gamification may be an effective and contextually relevant instructional strategy in Indonesian EFL (English as a Foreign Language) classrooms. The study highlights the potential of gamified instruction to support both affective and cognitive domains, and recommends further research on long-term impacts and scalable implementation models.